2019
DOI: 10.3126/nmcj.v21i1.24839
|View full text |Cite
|
Sign up to set email alerts
|

Community Based Screening for Diabetes and Prediabetes using the Indian Diabetes Risk Score among Adults in a Semi-Urban Area in Kathmandu, Nepal

Abstract: Diabetes has been recognized as a “global health emergency” with an estimated 9% of adults being affected. However, about half of these adults remain undiagnosed. Conventional screening tools like fasting plasma glucose (FPG), oral glucose tolerance testing (OGTT) and glycosylated haemoglobin (HbA1c) can be inconvenient and expensive in a community-based setting. The Indian Diabetes Risk Score (IDRS) is a simple, non-invasive tool which has been validated for use in the Indian population. Age, abdominal obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Within 95% confidence intervals, IDRS was able to identify between 62% to 77% of the persons with raised blood glucose in comparison to 78% to 97% for FPG. 16 Combining the IDRS with FCG estimation may increase the sensitivity and increase the yield during community based screening. 29 Amongst the study participants, a larger proportion of prediabetes was seen in comparison to undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within 95% confidence intervals, IDRS was able to identify between 62% to 77% of the persons with raised blood glucose in comparison to 78% to 97% for FPG. 16 Combining the IDRS with FCG estimation may increase the sensitivity and increase the yield during community based screening. 29 Amongst the study participants, a larger proportion of prediabetes was seen in comparison to undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It is comprised of four scored questions regarding age, abdominal obesity as measured by the waist circumference, family history of diabetes and physical activity levels. 15 During a study that was planned to assess the performance of the IDRS as a screening tool among an adult population in a semi-urban setting in the Kathmandu district, Nepal, 16 the performance of FCG was evaluated in comparison with FPG measurement in screening for diabetes and prediabetes. The concordance between FCG, FPG and 2 hr PG measurements was also assessed.…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation
“…10 Similarly, the prevalence of prediabetes in a community-based study done in Nepal, is reported to be 7.14%. 11 In our experience, prediabetes is often an incidental diagnosis in people who undergo a routine physical workup or perhaps a screening for diabetes.…”
Section: Nepalese Contextmentioning
confidence: 96%
“…For these reasons, community-based intervention programs are vital for investigating the actual outcome of lifestyle intervention that can be utilized as the prototype to develop the precise intervention in greater scale. Despite the fact that community-based intervention programs are catered for lifestyle changes, 4 only a few temple-based qualitative research studies were conducted especially topic related to lifestyle intervention owing to lifestyle modification is delicate due to it involves with knowledge, support, motivation, attitudes, behaviors, understanding and real practice, moreover, most of the existing researches associated with diabetes and/or hypertension lifestyle intervention at community-based level in Thailand were quantitative studies 2,3,5 -8 in a similar way of worldwide existing researches 9 -30 and current lifestyle interventions in Thailand seem less important for people to accept to use in their own lifestyle. For these reasons, hypertension and type 2 diabetes mellitus still spread out among Thai people.…”
Section: Introductionmentioning
confidence: 99%